Incidental abnormal bone marrow signal on magnetic resonance imaging and reflexive testing for the JAK2 V617F mutation - Langabeer, Stephen E. (Quantitative Imaging in Medicine and Surgery; Vol 8, No 8 (September 30, 2018): Quantitative Imaging in Medicine and Surgery, 2018)
With the increasing employment of imaging modalities in the diagnostic work up of patients comes an increase in the number of incidental cases with an abnormal bone marrow signal.